2013
DOI: 10.1186/1754-6834-6-48
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale analyses of butanol tolerance in Saccharomyces cerevisiae reveal an essential role of protein degradation

Abstract: Backgroundn-Butanol and isobutanol produced from biomass-derived sugars are promising renewable transport fuels and solvents. Saccharomyces cerevisiae has been engineered for butanol production, but its high butanol sensitivity poses an upper limit to product titers that can be reached by further pathway engineering. A better understanding of the molecular basis of butanol stress and tolerance of S. cerevisiae is important for achieving improved tolerance.ResultsBy combining a screening of the haploid S. cerev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 81 publications
(93 reference statements)
4
43
0
Order By: Relevance
“…Several previously published adaptive evolution approaches of S.   cerevisiae (such as for acetic acid and n-butanol tolerance) have shown that strains evolved in parallel experiments can have mutations affecting different sets of genes [44, 45]. Therefore, the results of the current study strongly suggest that UBR2 and GUT1 are absolutely crucial in the establishment of glycerol utilization capability in CEN.PK strains.…”
Section: Discussionsupporting
confidence: 50%
“…Several previously published adaptive evolution approaches of S.   cerevisiae (such as for acetic acid and n-butanol tolerance) have shown that strains evolved in parallel experiments can have mutations affecting different sets of genes [44, 45]. Therefore, the results of the current study strongly suggest that UBR2 and GUT1 are absolutely crucial in the establishment of glycerol utilization capability in CEN.PK strains.…”
Section: Discussionsupporting
confidence: 50%
“…This is in good agreement with previously published data on ethanol tolerance determinants which have also underscored the role of mitochondria [35,42,43]. Furthermore, protein degradation and retrograde signalling have recently been suggested as key factors in mediating butanol tolerance in yeast [44]. We find no evidence for increased proteolysis in our data, but it is possible that the increase we observe in mitochondrial proteins could be mechanistically linked to retrograde signalling as proposed by Gonzalez-Ramos et al [44].…”
Section: Resultssupporting
confidence: 91%
“…2012; González-Ramos et al. 2013). Therefore, availability of methods that enabled reintroduction of multiple point mutations at various genomic loci is invaluable for rapid identification of relevant mutations.…”
Section: Resultsmentioning
confidence: 99%